Sacramental Representation of the Priest in the Understanding of Ratzinger and Greshake - Hernández Rodríguez, Antonio Diego (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2022)
By ordination, the priest represents Christ sacramentally. By the same ordination, he can act on behalf of the Church. Joseph Ratzinger and Gisbert Greshake have reflected on what this representation entails, its deep origin and its concrete consequences in the life of the minister and in the Church as a whole. Both also do it with different positions, because while for Ratzinger the Christological representation is the key from which to understand the ecclesial ministry later, Greshake defends that in the minister there is a double representation as theological nucleus from which to understand and interpret the priesthood. This debate that took place in the last quarter of the last century is presented today from the articulation of the christological and pneumatological dimensions of the ministry.
Keywords: in persona Ecclesiae; in persona Christi; ministry; sacramentality; existence